Hestia-goddess of the hearth : the archetypal, architectural, and spiritual functions of the hearth as home of the human soul - Rich, Janet Bubar (Lewiston, NY : Edwin Mellen Press, 2014)
This book honors Hestia, the goddess of the hearth. It fills the gaping void in exclusive scholarship on Hestia and explores her as a pop culture icon in a quest to grasp her relevance for people today. Thinking about Hestia as an archetype of focus and centeredness may offer soulful refuge from the e-chatter overload that people face in their daily lives. It may help fulfill contemporary yearnings for authenticity and wholeness within human hearts and souls by offering us a path homeward, back to connections with people's inner selves.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 600, 650
Keywords: Vesta -- (Roman deity); Hestia -- (Greek deity); Home -- Miscellanea; Hearths -- Miscellanea; BODY, MIND & SPIRIT -- Spirituality -- Paganism & Neo-Paganism.; RELIGION -- Antiquities & Archaeology; Hearths; Hestia (Greek deity); Home; Vesta (Roman deity); Electronic books; Miscellanea